Pengaruh Mutu Pelayanan Terhadap Kualitas Pelayanan Serta Implikasinya Pada Kepuasan Pasien Rawat Jalan Poliklinik Jiwa - Husnah Latifah; Sri Rochani Mulyani; Rukhiyat Syahidin; Ahmad Yanwar Nugroho (Universitas Pahlawan Tuanku Tambusai, 2025)
Mental health disorders are increasingly becoming a pressing issue in Indonesia, especially in areas with limited access to adequate mental health services. Therefore, this study holds significant urgency in evaluating the quality of mental health services provided, to ensure that patients' needs are adequately met, as well as to provide recommendations for improving services to enhance patient well-being. This study aims to understand and analyze service quality, service performance, and patient satisfaction among outpatients at the Mental Health Clinic of RSUD Pakuhaji, Tangerang Regency. The research uses a quantitative method with data collection conducted through questionnaires. The results indicate that the service quality at RSUD Pakuhaji is fairly good in terms of the clarity of warning signs, but there is a lack of implementation of Standard Operating Procedures. The quality of service was rated positively regarding the healthcare workers' friendliness, although the cleanliness of the facility still needs improvement. Patient satisfaction was also rated well, particularly concerning the friendliness towards children, the elderly, and individuals with disabilities, although the use of internet technology for registration remains inadequate. The analysis shows that service quality has a positive and significant effect on both service performance and patient satisfaction, although the indirect effect of service quality through service performance on patient satisfaction is less significant. Improvements in specific aspects are expected to further enhance patient satisfaction.